Regulation by Dietary Carbohydrates of Intermediary Metabolism in Liver and Muscle of Two Isogenic Lines of Rainbow Trout - Song, Xuerong; Marandel, Lucie; Skiba-Cassy, Sandrine; Corraze, Geneviève; Dupont-Nivet, Mathilde; Quillet, Edwige; Geurden, Inge; Panserat, Stephane (Frontiers in Physiology, 2018)
Rainbow trout (Oncorhynchus mykiss) is recognized as a typical “glucose-intolerant” fish, and the limits of dietary carbohydrate utilization have been investigated for many years. In this study, the objective was to test the molecular effects of dietary carbohydrates on intermediary metabolism in two major metabolic tissues, liver and muscle. Another objective was also to study if the response to carbohydrate intake depended on the genetic background. We fed two isogenic lines of rainbow trout (named A22h and N38h) with high carbohydrate diet (carbohydrate, 22.9%) or low carbohydrate diet (carbohydrate, 3.6%) for 12 weeks. Carbohydrates were associated with higher feed utilization owned by the well-known protein-sparing effect, with better fish growth performance. However, atypical regulation of glycolysis and gluconeogenesis in liver and absence of hk and glut4 induction in muscle, were also observed. Regarding the effects of carbohydrates on other metabolism, we observed an increased, at a molecular level, of hepatic cholesterol biosynthesis, fatty acid oxidation and mitochondrial energy metabolism. Genetic variability (revealed by the differences between the two isogenic lines) was observed for some metabolic genes especially for those involved in the EPA and DHA biosynthetic capacity. Finally, our study demonstrates that dietary carbohydrate not only affect glucose metabolism but also strongly impact the lipid and energy metabolism in liver and muscle of trout.